An objective criteria used to support a practitioner's decision between sedation versus general anesthesia for the dental treatment of uncooperative pediatric patients. Issue 3 (December 2020) - Mohan, M.; Rosivack, R. Glenn; Masoud, Ziad; Burke, Mary J.; Markowitz, Kenneth; Merdad, Hisham
Abstract: Purpose: This purpose of this study was to create a criteria and assess its performance with the results as to use of conscious sedation versus general anesthesia for dental care of uncooperative pediatric patients. Methods: A retrospective study was designed to include children who received dental care under GA (General Anesthesia) or CS (Conscious Sedation) over a one year period in Newark, NJ. A study sample size of 80 children was created according to a power analysis used to yield a sample with 80% power at the 0.05 significance level. Children were divided into two groups. 35 subjects were in the CS group and 45 in GA group. For each child; the total score of the suggested criteria was calculated using the collected data. The suggested criteria combined seven scales, the criteria's total score is the sum of the seven scales' scores. The scale was designed such that a higher score would indicate the need for GA rather than CS. The criteria was designed to indicate the use of GA when the total score is 16 points or higher. Results: This evaluation showed that there is a positive correlation between the proposed criteria and the decision made retrospectively to use GA versus CS for uncooperative children needing dental care. Conclusion: The scale is a valid indicator of the need for GA versus CS, except for a child's age.